2018
DOI: 10.1161/hypertensionaha.117.10392
|View full text |Cite
|
Sign up to set email alerts
|

Two Pools of Epoxyeicosatrienoic Acids in Humans

Abstract: E poxyeicosatrienoic acids (EETs) are products of epoxygenation of arachidonic acid. They participate in cardiovascular regulation via vasodilator and natriuretic effects. Research on their actions used urine or plasma measurements of their 4 active regioisomers (5,8,11,and 14, and their relatively inactive derivatives, the dihydroxyeicosatrienoic acids [DHETs]. The latter are produced by enzymatic (soluble epoxide hydrolase [sEH]) or nonenzymatic (eg, pH, oxidative stress) degradation.Previous studies in anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…Although there is no proof for a deficit of epoxygenases in the CYP4A11 rs3890011 CC homozygous Black hypertensive patients, their aldosterone-independent ENaC hyperactivity and their responsiveness to amiloride strongly suggest that a similar mechanism may underlie their hypertension. This is consistent with otherwise documented decreased levels of EETs in salt-sensitive hypertension in Dahl rats and humans [ 10 ].…”
Section: Resistant and Refractory Hypertension The Role Of Enacsupporting
confidence: 92%
“…Although there is no proof for a deficit of epoxygenases in the CYP4A11 rs3890011 CC homozygous Black hypertensive patients, their aldosterone-independent ENaC hyperactivity and their responsiveness to amiloride strongly suggest that a similar mechanism may underlie their hypertension. This is consistent with otherwise documented decreased levels of EETs in salt-sensitive hypertension in Dahl rats and humans [ 10 ].…”
Section: Resistant and Refractory Hypertension The Role Of Enacsupporting
confidence: 92%
“…Blood was collected in EDTA tubes, centrifuged at room temperature, and separated immediately. Urine specimens for four periods (24-hour baseline, 24-hour salt loading, 12-hour furosemide-induced diuresis, and 12-hour salt depletion) were collected and refrigerated as described previously 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, other pools of EETs and DHETs in humans need to be considered. Studies on salt-sensitive blood pressure control in humans have found that urine EET and DHET levels represent the generation of EETs and DHETs in the kidney [9] . These urine EET levels were found to be involved in renal salt handling while plasma EET levels did not correlate with aldosterone and salt regulation [9] .…”
mentioning
confidence: 99%
“…Studies on salt-sensitive blood pressure control in humans have found that urine EET and DHET levels represent the generation of EETs and DHETs in the kidney [9] . These urine EET levels were found to be involved in renal salt handling while plasma EET levels did not correlate with aldosterone and salt regulation [9] . Interestingly, a role for kidney sEH to glucose regulation in type 1 diabetes and high fat diet induced insulin resistance in mice has been demonstrated [10] .…”
mentioning
confidence: 99%